Erring on the Margin of Error. - Thornton, Robert J.; Thornton, Jennifer A. (Southern Economic Journal, 2004)
The term “margin of error” is often erroneously explained in news articles reporting the results of public-opinion polls. We present here a number of representative examples of such misinterpretations drawn from the popular news media as well as from a number of authoritative Web sites (including that of the Gallup Organization) that explain the margin of error incorrectly. We suggest that encouraging students to search for, recognize, and correct misinterpretations of the margin of error can be a useful way of enhancing their understanding of sampling error, and we describe a number of classroom exercises that can help in this regard.